Predictive biomarkers of response to immune checkpoint inhibitors in hepatocellular carcinoma. (4th March 2022) - Muhammed, Ambreen; D'Alessio, Antonio; Enica, Andrei; Talbot, Thomas; Fulgenzi, Claudia Angela Maria; Nteliopoulos, Georgios; Goldin, Robert D.; Cortellini, Alessio; Pinato, David J.
ABSTRACT: Introduction: Hepatocellular carcinoma (HCC) is the most common primary liver cancer and fourth-leading cause of cancer death. While drug discovery to improve disease survival was historically poor, there is now evidence of significant potential for immune checkpoint inhibitors (ICPIs) in treatment of the disease, and indeed such drug approvals are beginning to emerge. Areas covered: HCC typically arises in the context of cirrhosis and chronic liver disease (CLD), and HCC exhibits significant biological heterogeneity, in part reflecting the broad range of etiologies of CLD. Different classes and combinations of ICPI-based therapy exist, but not all patients will respond and predictive biomarkers are not yet available to guide clinician decision-making, unlike some other cancer types. In this review, we discuss the emerging biomarkers for ICPI sensitivity in HCC, including tumor genomic features, perturbation of the gut microbiome, and systemic inflammatory markers. Expert opinion: Additional profiling studies are required to appreciate existing trends with clinical outcome and to further drive clinical studies in disease stratification by response. This will only be possible within collaborative and international efforts, especially regarding biopsy collection. A close collaboration between basic scientists and clinicians will be the key to shape the next future of HCC biomarker research.